The Societal Responsibility of the Companies and Financial Performance: An Unresolved Debate - Benazzou, L.; A. Nafzaoui, M. (International Journal of Engineering and Technology, 2019)
The purpose of this work is to examine the extent to which theÂ Societal Responsibility ofÂ Companies (SRC)Â affects their financial performance. The data used in this study are elicited from a survey questionnaire administered duringÂ a yearÂ to a sample of firms.The statistical tool developed for this research is the multiple regression analysis along with â€œthe quality of managementâ€ being used as a control variable. A principal components analysis has allowed us to show that the financial performance of businesses (FPB)Â is one-dimensional, whereas the SRC has three dimensions.The results of this research reveal two findings: one suggests that there is a positive link between SRC and the financial performance of businesses, the other highlights the negative correlation between these two variables.Â